187 Comparing lymph node staging modalities in high risk endometrial cancers: perioperative and long-term clinical outcomes in a community-based comprehensive cancer center. (13th November 2020) - Zhang, C; Meelheim, B; Deng, L; Chiu, S; Hussein, Y; Gattoc, L
Abstract : Objectives: There is limited data on survival outcomes for patients with high risk endometrial cancer (EC) undergoing sentinel lymph node (SLN) mapping to evaluate lymph node metastasis. Our study aims to compare operative and survival outcomes in high risk EC patients who underwent SLN mapping or lymphadenectomy (LND). Methods: From 2014–2020, we retrospectively compared all patients with pathology confirmed grade 3 or type II EC histology who underwent SLN or LND as part of their staging surgery. Kaplan-Meier estimates and Cox regression models were used to analyze and predict recurrence and survival outcomes. Results: 258 charts were reviewed. 102 and 103 patients were included in the SLN and LND groups, respectively. Demographics, cancer stage and histology were not statistically different between groups (p>0.05). SLN detection rate was 97.1%. Bilateral mapping was achieved in 87.3% of patients. Nodal metastasis occurred in 22.5% in the SLN group and 24.3% in the LND group (p>0.05). Rates of adjuvant therapy were similar. Median follow up for the SLN group was 13.5 months and 15.5 months in the LND group. PFS rates were 75.7% and 78.0% (p=0.67) and OS rates were 91.3% and 91.7% (p=0.58) for SLN and LND groups, respectively. A multivariate cox proportional hazards regression showed stage I disease was protective against recurrence (HR 0.24, 95% CI 0.08–0.72) and death (HR 0.13, 95% CI 0.02–0.84) Conclusions: This preliminary data demonstrates a high SLN detection rate in patients with high risk EC and no significant differences in PFS or OS as compared to LND.